Metaphorization in the Ukrainian Media Discourse in 2022–2023: External Factors, Dynamic Processes, Communicative and Intentional Dimensions - Kostusiak, Nataliia; Shulska, Nataliia; Sadivnychyi, Volodymyr; Sydorenko, Nataliia; Zdikhovska, Tetiana; Iovkhimchuk, Nataliia; Bondarenko, Olena (My University, 2023)
The article analyzes the metaphors selected from the media texts of 2022– 2023; it is found that they not only perform an informative role, but also implement a number of communicative strategies and pragmatic-intentional tasks. A detailed analysis of the corpus of actual material made it possible to single out the most important features of figuratively used units, among which there are the reinterpretation of known images and concepts based on associative connections, the transmission of hidden content, evaluability, emotional and expressive coloring, often going beyond the canons of newspaper journalism, sometimes “shaking” stylistic norms. It was found that in the Ukrainian media discourse of 2022–2023, metaphors with a different thematic range are presented, the emergence of which is based on stereotypes of the perception of modern reality, in particular, military actions in Ukraine. A significant group consists of zoomorphic and mythomorphic metaphors – secondary names of enemies and the president of Russia. In order to strengthen the negative coloration, attributive, in particular occasional, units function alongside them, which give the texts an ironic-sarcastic sound, mare them sound as colloquial speech, sometimes even vulgarize them. It is noted that the use of several metaphorically designed secondary names, which implement the stylistic technique of gradation, is aimed at achieving this goal. Attention is focused on verbs that, modeling the behavioral stereotypes of the enemy army, not only contribute to the creation of an objective image of the invaders, but also convey irony and sarcasm. Among the words of this part-language class, colloquial forms dominate, which serve as a powerful journalistic tool and exert a communicative influence on the reader. The expressive means of linguistic aggression include anthropomorphic metaphors built on the attribution of actions, signs, and characteristics inherent in a person to war and Russia. It has been revealed that in journalistic texts, lexemes of the culinary and gastronomic sphere, which are presented in publications about the destruction of Russian, less often Belarusian enemies and their equipment, undergo metaphorization.
Keywords: lexeme; secondary nomination; metaphor; figurative meaning; emotional evaluation; noun; verb; language of mass media; media discourse; Ukrainian language